Implementasi Good Governance Terhadap Kualitas Penyelenggaraan Pelayanan Kecamatan di Kota Pekalongan - Adi Kurniawan Saputra; Jeki Trimarstuti (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2021)
The government as the provider of public services often creates dissatisfaction for the community, this shows that there is still a lack of implementation of good governance, which can lead to maladministration and harm the community. The purpose of this study was to describe the conditions of the implementation of Good Governance on the process of public services and the quality of public services provided by the District government to the community. The research method used is descriptive qualitative in order to explore the problems and modes of public service delivery in sub-district units. Based on the research findings, it shows that overall the implementation of public services observed from 9 aspects or elements in the four sub-districts in Pekalongan City can be said to be relatively good enough and even good in its implementation. In general, the problems that are obtained from the results of all observed aspects that occur in the four (4) districts are related to the 6th point of implementing competence, the 8th point of complaint handling, and the 9th point of infrastructure. The results of this study indicate that descriptively, the implementation of Good Governance which is observed from the aspects of transparency and accountability has generally been applied in the organization of the four sub-districts in Pekalongan City but has not been fully implemented properly. Meanwhile, inferentiallly the implementation of Good Governance has a positive and significant effect on public services in the four districts with different levels of influence in each District Office.